Materialism and Environmental Knowledge as a Mediator for Relationships between Religiosity and Ethical Consumption - Novi Sekar Sari; Ririn Tri Ratnasari; Ismah Osman; Ega Rusanti (Jurnal Ekonomi Syariah Teori dan Terapan, 2023)
ABSTRACTOn a global and regional scale, Indonesia has one of the least environmentally sustainable economies in the Asia-Pacific region. Consumption is one of the key factors contributing to environmental degradation. By using materialism and environmental knowledge as mediators, this study aimed to understand how religiosity affects ethical consumption. This research used quantitative methods with structural equation modeling (SEM) analysis techniques based on partial least squares (PLS). The data came from a questionnaire distributed online. 153 valid questionnaires were selected for analysis. All respondents came from Indonesia, were adults (from 18 years old), and were Muslims. Findings show that religiosity influences ethical consumption, materialism, and environmental knowledge. This research also reveals that materialism and environmental knowledge influence ethical consumption, as well as the mediating effect of materialism and environmental knowledge on the influence between religiosity and ethical consumption. So, all hypotheses from this research can be accepted. These findings contribute theoretically to explaining the relationship between religiosity, materialism, environmental knowledge, and ethical consumption. Thus, this findings contribute to the field of Islamic economics. Practically, the findings of this research can help marketers formulate communication strategies that take into account the level of religiosity of consumers in Indonesia. Marketers must avoid unethical practices to encourage ethical consumption.Keywords: Religiosity, ethical consumption, materialism, environmental knowledge ABSTRAKPada skala global dan regional, Indonesia merupakan salah satu negara dengan perekonomian paling tidak ramah lingkungan di kawasan Asia-Pasifik. Konsumsi merupakan salah satu faktor utama yang berkontribusi terhadap degradasi lingkungan. Dengan menggunakan materialisme dan enviromental knowledge sebagai mediator, penelitian ini berupaya memahami bagaimana religiosity mempengaruhi ethical consumption. Penelitian ini menggunakan metode kuantitatif dengan teknik analisis Structural Equation Model (SEM) berbasis Partial Least Square (PLS). Data berasal dari kuesioner yang disebarkan online. 153 kuesioner yang valid dipilih untuk analisis. Seluruh responden berasal dari Indonesia, dewasa (mulai 18 tahun) dan beragama Islam. Temuan menunjukkan bahwa religiosity berpengaruh terhadap ethical consumption, materialism, dan environmental knowledge. Selain itu juga diketahui bahwa materialism dan environmental knowledge berpengaruh ethical consumption, serta adanya efek mediasi dari materialism dan environmental knowledge pada pengaruh antara religiosity dan ethical consumption. Sehingga, semua hipotesis penelitian ini dapat diterima. Secara praktis, temuan penelitian ini dapat membantu pemasar untuk merumuskan strategi komunikasi yang mempertimbangkan tingkat religiosity konsumen di Indonesia. Pemasar harus menghindari praktik tidak etis untuk mempromosikan ethical consumption.Kata Kunci: Religiosity, ethical consumption, materialism, environmental knowledge